Handbook of renal and pancreatic transplantation - MacPhee, Iain; Fronek, Jiri (John Wiley & Sons, 2012)
This book is designed to fill the need for a contemporaryhandbook for the practice of renal and pancreatic transplantation thatis focussed on a European rather than North American approach. There are significant differences in transplant practice internationally andthere is a need for a practical guide to application of the current evidencebase.